MISTAKES IN LEARNING A FOREIGN LANGUAGE AND THEIR INTERACTIVE SOLUTIONS (Journal of Universal Science Research, 2024)
Today, in the era of rapid development and globalization, the demand for young personnel who master the days is increasing as production increases. This is the basis for popular young people to increase their interest in languages ​​and learn foreign languages. But a number of mistakes are made in the process of learning languages ​​produced by students. In this article, we will analyze some of the mistakes, problematic products and documents that young people who are new to developing languages ​​make.